Patient's Perspective of Eye Service Quality in Yogyakarta's Teaching Hospital - Dhimas Hari Sakti; Indra Tri Mahayana; Firman Setya Wardhana; Dwima Faiqa Nafisha; Dhimas Ali Firman; Novika Handayani; Tiara Putri Utami (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2018)
Introduction : The eye care service in The Dr. Sardjito Hospital has one of the highest number of patients amongst other health care services provided. Thus evaluation of the patients' satisfaction upon the service provision is needed to improve the quality of the eye care service. Methods : A cross-sectional study was performed in the ophthalmology outpatient clinic at the teaching hospital in Daerah Istimewa Yogyakarta, Indonesia. Interviews were conducted on 77 patients using Patient Satisfaction Questionnaire Short Form (PSQ-18) in 2017. Results : Overall, patients were mostly satisfied with the interpersonal manner of the doctors (mean : 4.12  0.42) and least satisfied with the time spent with doctors (mean : 3.310.95). There was a statistically significant difference among each subscale (p=0.000). Gender, income, occupation, and education had no significant statistical difference to the aspects of quality. However, significant differences were found in the financial aspects of marital status, education level, and co-diagnoses group with p-value of 0.009, 0.043, and 0.048 respectively. Conclusions : Patient satisfaction could be improved by increasing the time spent at each visit with the doctor. Meanwhile, financial aspect is mostly affected by the patients’ background. This study needs to be continued to get wider perspectives on the larger population sample of eye patients. Therefore, the quality of eye care services may be improved.